Abdominal catastrophe secondary to paraduodenal hernia - Mathew, Cherian; Reddy, Sai Kiran; Kumar, Binoj; Hanumappa, Harish Kumar; K, Sooraj; Treasa Poulin, Mary; -, Sahira (Indian Journal of Case Reports, 2019)
An Internal hernia is a protrusion of abdominal viscera through the opening in the peritoneum or mesentery. We report the case of a left paraduodenal hernia (LPDH) combined with a small bowel obstruction in a 50-years-old male with pain abdomen and vomiting and no previous abdominal surgeries. An anteroposterior abdominal radiograph showed a clustered small bowel loops towards the left side of the abdomen and few air-fluid levels suggestive of obstruction. CECT abdomen showed a focal crowding of small bowel loops noted in the left anterior pararenal space with crowding of mesenteric vasculature and displacement of ascending left colic artery and inferior mesenteric vein anteriorly. The surgical intervention provided definitive diagnosis and treatment for LPDH. A paraduodenal hernia is a relatively rare cause of acute abdomen, and its diagnosis is often incorrect or delayed owing to its variable clinical manifestations. Therefore, it is important for the clinicians to recognize this condition, diagnose it early, and avoid making a wrong diagnosisowing to its high overall mortality rate.